2020
DOI: 10.1159/000507268
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Surgical Margin Positivity after Radical Prostatectomy in the Turkish Population: A Multicenter Study of the Urooncology Association

Abstract: Background: The prediction of positive surgical margins (SM) after radical prostatectomy (RP) is important for planning the surgical modality and adjuvant therapy in patients with prostate cancer (PCa). Objectives: To investigate factors affecting SM positivity in patients diagnosed with PCa who underwent RP using the PCa database of the Urooncology Association (Turkey). Methods: Patients who underwent RP due to clinically T1c-T3 PCa and who had detailed SM data for the RP specimen were included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Then, 295 full-text articles were further examined and 268 articles were excluded because 27 articles included the same cohort of patients and 241 articles lacked enough data for further research. Finally, 27 articles ( 8 , 15 40 ) published between 2009 and 2020 were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Then, 295 full-text articles were further examined and 268 articles were excluded because 27 articles included the same cohort of patients and 241 articles lacked enough data for further research. Finally, 27 articles ( 8 , 15 40 ) published between 2009 and 2020 were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by limited sample size and that the obese subgroup had the fewest number of patients. However, other studies suggest that there might be a detrimental effect of high BMI on PSM (5,6,24).…”
Section: Discussionmentioning
confidence: 96%
“…It is commonly accepted that adverse preoperative tumor characteristics such as clinical stage (cT), Gleason score and PSA are associated with adverse perioperative results, such as increased blood loss, increased operation (OR) time, positive surgical margins (PSM) or lower probability of neurovascular bundle preservation (NVBP) ( 3 , 4 ). However, non-tumor-related adverse patient characteristics such as obesity or high prostate volume might also deteriorate perioperative results ( 5 , 6 ). This seems even more relevant as adverse perioperative results represent strong predictors of long term oncological and functional outcomes after RP ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…They believe that biopsy PNI could predict PSM independent of PSA and Gleason score. Çelik et al (Çelik et al, 2020) biopsy PNI was found to be independent predictor for PSM and the number of PSM locations. But, Cannon et al (Cannon et al, 2005) found that biopsy PNI was associated with extraprostatic extension but did not predict the prognosis of radical prostatectomy with preserved NVB and positive surgical margins.…”
Section: Discussionmentioning
confidence: 95%
“…Since our study revealed that biopsy PNI was a predictor of PSM of prostate cancer, It also correlated with the number of positive incisional margin locations. In addition, positive posterior lateral surgical margins were associated with biopsy PNI and the surgical approach to nerve preservation (Çelik et al, 2020). The nerve‐sparing RP approach is performed to protect erectile function after surgery.…”
Section: Discussionmentioning
confidence: 99%